The Pre-Investigation Stage of the ICC : Criteria for Situation Selection - Stegmiller, Ignaz (Berlin : Duncker & Humblot, 2011)
With the first part of this study Ignaz Stegmiller provides an introduction to the problem of pre-investigations, the second part gives an overview of the OTP's structure. Part III addresses how the selection process is performed. In this part, the complexity of pre-investigations is revealed. The three trigger mechanisms - State referrals, SC referrals, and the proprio motu mechanism - are illustrated, Self-referrals are critically analyzed and the author argues that the Prosecutor should use his proprio motu power more frequently. Perceptions of OTP's lack of independence must be rebutted. The proprio motu tool could have a great share in that, while the self-referral practice is associated with nepotism. Part IV analyses the criteria used to select situations including Article 53. As regards admissibility, the two notions of complementarity and gravity can be distinguished. Bearing in mind the inactivity criterion, complementarity is basically analyzed in a threefold manner: (1) as a rule whereby situations and cases are admissible if the State remains inactive; (2) exceptions as found in articles 17 (1) (a)-(c), 20 (3), which can lead to inadmissibility; (3) in turn, article 17 (2), (3) provides "exceptions to the exceptions" if a State is unwilling or unable to genuinely carry out proceedings. Gravity is a very complex notion. The author differentiates two concepts: "legal" and "relative" gravity. Legal gravity must then be linked to article 53 (1) (b) and relative gravity is part of article 53 (1) (c)'s assessment of the "interest of justice." Only a broad application of the "interest of justice" gives the OTP the flexibility that it needs. Parts V and VI then summarize the most important results of this study
Keywords: Criminology & Criminal Justice